Creditors - Arowosaiye, Yusuf Ibrahim; Masum, Ahmad; Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan (Sweet & Maxwell, Thomson Reuters, 2025)
In the modern world, where most companies are aspiring to expand their investment and optimise returns, additional capital is needed to achieve this goal. Companies also need access to funds to function effectively and to maintain its day- to- day activities. In the absence of sufficient capital to finance the operations of the companies, seeking additional working capital from external sources becomes the alternative option. The most common approach to deal with insufficient working capital by companies is through credit financing (loans with interest) from creditors. Because of this credit financing arrangement, creditors become significant stakeholders with reasonable influence over the efficient operation of the company and the protection of its assets. To encourage lending and boost the inflow of funds into businesses, it is crucial to protect the interests of those who provide capital. This can be achieved through the implementation of laws, processes, and procedures that meet creditors’ needs and safeguard the assets of corporate debtors. Such protective measures act as a collective safeguard for creditors, playing a vital role in encouraging them to provide loans to companies. Without adequate protection, creditors may become hesitant to lend to businesses in dire need of financing. Since companies often rely on creditors for funding to effectively operate, particularly when their ambitions for expansion and the scale of business activities and investments require significant external capital, it is crucial to establish a legislative and procedural framework that protects the interests of creditors who provide this funding, especially in situations where the company’s actions might undermine or jeopardise those interests. Under the Companies Act 2016 (“CA 2016”), creditors are afforded certain rights and protections to ensure their interests are safeguarded in relation to companies that are undergoing financial distress or liquidation. The CA 2016 provides a legal framework designed to balance the rights of creditors with the need to promote business efficiency and growth. The protection mechanisms are critical to maintaining the integrity of business transactions and ensuring that creditors are treated fairly in instances of insolvency or corporate restructuring. This chapter delves into the rights and protections afforded to corporate creditors under the CA 2016. Additionally, it explores the legislative measures and approaches within Malaysian corporate law designed to safeguard the interests of corporate creditors, ensuring that their stake is adequately protected in the face of potential risks.